Potential Opportunities of Educational Environment in Developing Tolerance in Students (Texas Journal of Philology, Culture and History, 2023)
This article analyzes the role of the family entity in improving tolerance competencies, the potential opportunities of the educational environment and pedagogical strategies for developing tolerance in students, and a number of methods for developing tolerance in the teacher are presented. Also, a number of pedagogic strategies required in the educational process at a higher educational institution for the development of tolerance competence in students have been developed and scientifically substantiated